The family Melicharidae (Acari, Mesostigmata) in Slovakia, with description of new species, annotated faunal synopsis and identification keys of species from Europe - Mašán, Peter (Zootaxa, 2022)
The mites of the family Melicharidae (Acari: Mesostigmata) collected in Slovakia are reviewed. Sixty-one species belonging to five genera were recorded, of which thirty-three are new to science and fifteen are new to the Slovak fauna. All species are revised and rediagnosed, and an extensive set of photomicrographs (more than 1,300 images arranged in 337 Plates) is provided for their identification. Information on habitat and regional distribution is provided for each species. Proctolaelaps (fifty-three species) is the most species-rich and morphologically heterogeneous genus in the family. The following thirty-three new species are proposed and described: Mycomelichares triplacis sp. nov., Proctolaelaps appendiculatus sp. nov., Proctolaelaps bivalvifer sp. nov., Proctolaelaps bombi sp. nov., Proctolaelaps bucinator sp. nov., Proctolaelaps calycinus sp. nov., Proctolaelaps carnifex sp. nov., Proctolaelaps conifericola sp. nov., Proctolaelaps coralifer sp. nov., Proctolaelaps cryptopteryx sp. nov., Proctolaelaps dendroctonoides sp. nov., Proctolaelaps dorci sp. nov., Proctolaelaps dorcisimilis sp. nov., Proctolaelaps fagi sp. nov., Proctolaelaps falcarius sp. nov., Proctolaelaps fragilis sp. nov., Proctolaelaps fusifer sp. nov., Proctolaelaps hemisphaericus sp. nov., Proctolaelaps laeviusculus sp. nov., Proctolaelaps myrmecophilus sp. nov., Proctolaelaps orolaelapoides sp. nov., Proctolaelaps oxyodon sp. nov., Proctolaelaps pcolai sp. nov., Proctolaelaps pelticola sp. nov., Proctolaelaps populi sp. nov., Proctolaelaps quadridens sp. nov., Proctolaelaps sacculiger sp. nov., Proctolaelaps sagittarius sp. nov., Proctolaelaps serpentarius sp. nov., Proctolaelaps spanius sp. nov., Proctolaelaps speluncarum sp. nov., Proctolaelaps tubisaccus sp. nov., and Proctolaelaps tulipifer sp. nov. Nineteen new species are recognized in the present work, which were previously thought to belong to a single species, Proctolaelaps pygmaeus (J. Müller, 1859). The species boundaries of these species are often only weakly determined by some external morphological characters, but well definable and recognizable by the morphology of the internal structures of the sperm access system in the female (the same is true for the species related to Proctolaelaps hystrix). Proctolaelaps bulbicolus (Oudemans, 1929), Proctolaelaps convivus (Berlese, 1916), Proctolaelaps fissuratus (Berlese, 1916), Proctolaelaps laevisternus (Berlese, 1916), Proctolaelaps sopalit (Samšiňák, 1958), Proctolaelaps vulgaris (Pinchuk, 1972), and Proctolaelaps ovatus (Ma, Ning & Wei, 2003), previously suspected to be junior synonyms of Proctolaelaps pygmaeus (J. Müller, 1859), are here considered as unrecognizable species, relegated to the species incertae sedis, or species related within the invalid genus Proctofissus Karg, 1979. The very broad concept of the genus Proctolaelaps does not reflect the phylogenetic relationships within the apparently morphologically heterogeneous species, and it needs a thorough revision. As documented in present work, the genus includes species with different types of sperm access system: for example, species in the hystrix group possess the “laelapoid-type” of the sperm access system, whereas species related to Proctolaelaps pygmaeus (here placed in the pygmaeus group) have a highly modified sperm access system derived from the “phytoseioid-type”, with two separate parts each associated with coxa III and clearly not connected by a medial structure called the “sacculus foemineus” (a specific component of the laelapoid-type sperm access system). The taxonomy includes four new specific synonyms as follows: Proctolaelaps arctorotundus Nikolsky, 1984 = Proctolaelaps epuraeae Hirschmann, 1962, Proctolaelaps pruni Karg, 1988 = Proctolaelaps eccoptogasteris (Vitzthum, 1923), Proctolaelaps pseudofiseri Nikolsky, 1984 = Proctolaelaps fiseri Samšiňák, 1960, and Proctolaelaps ventrianalis Karg, 1971 = Proctolaelaps intermedius Athias-Henriot, 1959. Melichares biebrzae Gwiazdowicz, 2005 is newly placed in Proctolaelaps Berlese, 1923. The genus Orolaelaps De Leon, 1963, previously known from North and South America, is reported from Europe for the first time, introduced by an invasive cosmopolitan species Stelidota geminata (Say), the strawberry sap beetle of the family Nitidulidae. The following species are reported from Slovakia for the first time, namely Orolaelaps quisqualis De Leon, 1963, Proctolaelaps bickleyi (Bram, 1956), Proctolaelaps biebrzae (Gwiazdowicz, 2005), Proctolaelaps cossi (Dugès, 1834), Proctolaelaps cossoides Faraji, Sakenin-Chelav & Karg, 2007, Proctolaelaps hystricoides Lindquist & Hunter, 1965, Proctolaelaps izabelae Faraji, 2011, Proctolaelaps jueradeus (Schweizer, 1949), Proctolaelaps longanalis (Westerboer, 1963), Proctolaelaps rotundus Hirschmann, 1962, and Proctolaelaps xyloteri Samšiňák, 1960. The records of Proctolaelaps bombophilus (Westerboer, 1963), Proctolaelaps epuraeae Hirschmann, 1962, Proctolaelaps pomorum (Oudemans, 1929), and Proctolaelaps scolyti Evans, 1958 were previously based on misidentified specimens and are now supported by new reliable findings [in contrast to Proctolaelaps hystrix (Vitzthum, 1923) and Proctolaelaps pini Hirschmann, 1963, which were not definitely confirmed by the present work in Slovakia]. New dichotomous keys are given for the identification of sixty-eight species from seven genera found so far in Europe (Melichares Hering, 1838, Mucroseius Lindquist, 1962, Mycolaelaps Lindquist, 1995, Mycomelichares Mašán & Joharchi, 2021, Orolaelaps De Leon, 1963, Orthadenella Athias-Henriot, 1973, and Proctolaelaps Berlese, 1923).